Analisis Faktor Keberhasilan Kolaborasi Triple Helix: Perspektif Industri - Budi Irawan; Elisa Anggraini; Joko Purwono (Politeknik Ganesha Medan, 2025)
This research identifies and evaluates the key success factors for Triple Helix collaborations (academia, industry, and government) from the perspective of the industrial sector. The research is contextualized within an industry-driven Open Innovation model, where 19 national-scale companies, including state-owned and private enterprises, partner with the Indonesia Endowment Fund for Education (LPDP) to address industrial innovation challenges. Within this framework, LPDP and its industry partners invite university research teams to compete for funding based on industry-proposed themes. Primary data were collected through an online survey of 107 industry professionals, representing diverse hierarchical levels (from staff to top management) across strategic sectors such as energy, agribusiness, pharmaceuticals, defense, and telecommunications. Respondents assessed 21 success factors using a 1-to-10 Likert scale. Quantitative data were analyzed using SPSS to calculate the mean rank of each factor, which were then categorized into five levels of importance. Concurrently, qualitative data from open-ended questions were visualized as a word cloud using NVivo. The principal findings indicate that industry prioritizes transparency (the absence of hidden agendas), knowledge sharing, and the alignment of research objectives with realistic implementation pathways. Furthermore, qualitative results emphasize the need for government support to simplify product certification regulations and recommend market potential analysis to enhance research commercialization. This study offers crucial managerial implications for all Triple Helix stakeholders by identifying the most decisive factors in fostering successful and impactful collaborations.